Effectiveness of Localized English Content in Developing Cognitive Skills among IX Standard Students - Idayaraja, T. (University of Jaffna, 2025)
This study investigated the effectiveness of localized English content in developing cognitive skills among IX standard students. Recognizing the intrinsic link between language learning and cognitive processes such as memory, attention, problem-solving, and critical thinking, this research addressed the gap in understanding how localized English content, with its unique linguistic and cultural features, influences cognitive development. Despite the acknowledged benefits of localized content, its specific impact on cognitive skills remains under-explored. Drawing upon constructivist learning theory and empirical evidence from successful English language learning through cultural immersion, this study hypothesized that instruction utilizing localized content would significantly enhance cognitive skills compared to conventional content. The objective was to determine the effectiveness of localized English content, compared to traditional English content, in enhancing the remembering, understanding, applying, analyzing, evaluating, creating, attention, and problem-solving skills of IX standard students. A localized English content unit, “Our Village Economy and Culture,” was developed, focusing on the students’ local economic activities and festivals. Subject experts evaluated the unit for clarity, usefulness, language, style, aesthetic appeal, illustrations, presentation, consistency, and suitability. Valid and reliable cognitive skills assessment tools were also developed and evaluated. A quasi-experimental design, employing purposive sampling through a matched-pairing technique, was used to assign 40 participants to experimental and control groups. Both groups underwent pre- and post-tests. The experimental group received instruction using the localized content, while the control group used traditional English content. Identical teaching and learning activities were implemented across both groups to ensure a fair comparison. A t-test was used to analyze the significant differences between the two groups’ post-test scores. The analysis revealed a statistically significant improvement in the cognitive skills scores of the experimental group compared to the control group. The results indicated that students in the experimental group, who received instruction using localized English content, demonstrated significantly greater development in cognitive skills compared to the control group. These findings suggest that incorporating locally relevant and culturally embedded materials is an effective strategy for fostering cognitive development among students.
Keywords: Cognitive skills; Cultural features; Local economic and cultural activities; Localized English content